The role of immature granulocyte percentage in predicting acute chest syndrome and the severity of the vaso-occlusive crisis in sickle cell disease - Karahan, Feryal; Ünal, Selma; Topçu, Dilara Bal; Öztaş, Yeşim; Bozlu, Gülçin (The Turkish Journal of Pediatrics, 2022)
Background. Sickle cell disease (SCD) is an inflammatory disease that can result in both chronic and acute inflammation. Immature granulocytes (IG) are not-yet-mature white blood cells that can be easily detected in complete blood count (CBC) tests. In recent studies it has been suggested that IG may play a role in determining the prognosis of inflammatory diseases. The aim of our study was to investigate the role of IG percentage on predicting acute chest syndrome (ACS) and the severity of vaso-occlusive crisis (VOC) in patients with SCD. Methods. The study cohort consisted of 49 SCD patients admitted to the emergency department for VOC. If symptoms did not regress despite appropriate treatment including hydration and analgesia, they were hospitalized. Patients whose symptoms regressed were discharged from the emergency department within 24 hours. Blood samples, including CBC and C-reactive protein (CRP), a marker of inflammation, were taken within the first hour of admission. Steady state laboratory parameters from the previous visit in the last three months were collected from patient files. Results. The mean age was 18±4 (range 8-25) years. Most were hospitalized (41/49; 83.7%) and 8 of 49 were discharged from the emergency department after their treatment for VOC. ACS developed in 13 of 49 (26.5%). White blood cell, neutrophil and nucleated red blood cell counts, percentage of IG (IG%) and CRP levels were significantly increased in patients with VOC. IG% of patients with ACS was significantly higher than patients without ACS. However, ROC analysis showed that IG% was not associated with the development of ACS or hospitalization for VOC. Conclusions. Despite a small SCD cohort, the significant increase in the IG% in patients with VOC compared to their baseline values has suggested a role for IG% in predicting VOC. Although IG% was higher in ACS, its utility in predicting ACS was poor.
Keywords: immature granulocyte; inflammation; sickle cell disease